Genomic Approaches to Using Diversity for the Adaptation of Modern Varieties of Wheat and Barley to Climate Change - Neumann, Kerstin; Schulthess, Albert W; Bassi, Filippo; Dhanagond, Sidram; Khlestkina, Elena; Börner, Andreas; Graner, Andreas; Kilian, Benjamin (Taylor & Francis, 2023)
Plant genetic resources have contributed to the identification and characterization of key loci and genes for important agronomic traits such as flowering time, plant height, root and shoot growth and resistance to abiotic stresses. Key loci for pre-anthesis growth vigor and drought tolerance have been revealed by genome-wide mapping in three diverse barley panels. Recent studies have identified candidate loci for biomass and/or the corresponding growth rates, water use efficiency, root traits, tiller number, plant height under drought or/and well-watered conditions using destructive and non-invasive 48phenotyping. In all three panels, 76 genomic regions were identified in at least two panels in which QTLs for growth and/or drought tolerance cluster, some marker-trait associations were even found for identical SNPs in all panels. The main genomic regions identified in three different mapping panels for trait complexes such as growth vigor, root architecture and pre-anthesis drought tolerance are highly relevant for future research on adaptation to climate change.